In Vitro Proof of Concept Evaluation of a Gravity Powered Novel Filtration Device to Effectively Process a Blood Analogue/Particle Mixture to Rapidly Produce a Clear Filtrate - Horowitz, Michael Bruce; Repko, Brandon; Le, Hieu; Bobo, Benjamin; Pande, Henre (Cardiology and Cardiovascular Medicine, 2024)
Background: This study provides an In Vitro proof of concept evaluation of a gravity powered novel blood filtration device to effectively process a high viscosity whole blood analogue/particle mixture to rapidly produce a clear filtrate. Methods: A novel proprietary gravity fed blood filtration system was used to process a particulate filled water/glycerol high viscosity whole blood analogue to determine the device’s ability to rapidly exclude foreign body and to produce a cleared filtrate. Results: This study demonstrated 100% filtration of 2.3 mm, 63-75 micron and 355-425 micron spheres from a high viscosity blood analogue/particle mixture using a gravity fed three filter system. Filtration rate using a clear solution that mimics high viscosity whole blood occurred at a rate of 100 cc/4-7 seconds (> 500 cc/minute). Conclusion: A gravity driven three filter device can rapidly process a high viscosity whole blood equivalent fluid/particulate mixture. Results from this and prior In vitro studies indicate that such a device may prove useful for the reinfusion of autologous blood lost during invasive procedures. Trial Registration: This article does not report the results of a health care intervention on human subjects. .